Results on stakeholder involvement in planning a LL4P in Kenya using net-mapping and Fuzzy Cognitive Maps (FCM) - Kibet, Walter; Habermann, Birgit; Ewell, Hanna; Nehring, Ryan; Kumar, Praveen; Mwambi, Diana; Ngeno, Vincent; Kachilei, Levy (International Livestock Research Institute, 2024)
CGIAR Research Initiative on “Low-emission Food Systems (Mitigate+)” WP3 on Living Labs for People 8 AM –9:30 AM EST, December 9, 2024. Zoom meeting